Testing the Weak Equivalence Principle with an antimatter beam at CERN. (July 2015) - Kimura, M; Aghion, S; Amsler, C; Ariga, A; Ariga, T; Belov, A; Bonomi, G; Bräunig, P; Bremer, J; Brusa, R S; Cabaret, L; Caccia, M; et al.
Abstract: The goal of the AEgIS experiment is to measure the gravitational acceleration of antihydrogen – the simplest atom consisting entirely of antimatter – with the ultimate precision of 1%. We plan to verify the Weak Equivalence Principle (WEP), one of the fundamental laws of nature, with an antimatter beam. The experiment consists of a positron accumulator, an antiproton trap and a Stark accelerator in a solenoidal magnetic field to form and accelerate a pulsed beam of antihydrogen atoms towards a free-fall detector. The antihydrogen beam passes through a moiré deflectometer to measure the vertical displacement due to the gravitational force. A position and time sensitive hybrid detector registers the annihilation points of the antihydrogen atoms and their time-of-flight. The detection principle has been successfully tested with antiprotons and a miniature moiré deflectometer coupled to a nuclear emulsion detector.